The Role of Job Satisfaction in Mediating the Influence of Organizational Practices on Employee Performance: A Study of the PIR-Based Sandwich Panel Industry - Sopyandi, Depi; Eddy Nugroho, Rosalendro; Shilul Imaroh, Thukas (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to investigate how organizational practices including quality management systems, occupational health and safety (OHS), workplace facilities, and green work environments directly and indirectly affect employee performance, with job satisfaction serving as a mediating variable. The research responds to the increasing demand for sustainable and employee-centered operations in the sandwich panel manufacturing industry. Methodology/approach – This research adopts a quantitative explanatory design and applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from 150 permanent employees of a sandwich panel manufacturing company in Indonesia. The analysis includes both primary survey responses and secondary records of customer complaints and workplace accidents over a five-year period. Findings – The results reveal that quality management and OHS systems have significant direct effects on employee performance, while workplace facilities and green environments demonstrate a more modest influence. Job satisfaction significantly mediates the relationship between all organizational practices and employee performance, highlighting its central role in performance optimization. Novelty/value – This study contributes to the literature by integrating quality, safety, and sustainability-oriented workplace factors into a unified performance model, emphasizing the mediating function of job satisfaction. The findings align with and support several Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work), SDG 9 (Industry Innovation), and SDG 12 (Responsible Consumption and Production).